Research of Mechanical Property of Trochoid Roller Pinion Rack Transmissions - Zhang Yun; Zhang Peng; Bao Bingbing (Jixie chuandong)
It is important to meet drive requirements of the high precision,high speed and long-stroke for robotic driving system. An investigation on meshing force and contact stress of trochoid roller pinion rack transmission is carried out. Firstly,the mechanical model of meshing pair is established when considering statically indeterminate problem of multi-tooth meshing transmission,and the time-variant calculating formula and change of meshing force is derived,and force distribution between rollers is analyzed according to the equilibrium conditions of moment and the analysis of pressure angle. Then,the calculating formula and change of stress is concluded based on the Hertz formula of elastic mechanics and radius of curvature of the contacting point. Finally,a example is given and the finite element models of meshing pair are established. Through the finite element simulation of the meshing process of roller and trochoid tooth,the rationality of the mechanics modeling method and the analysis results of the meshing pair are verified.